The role of forgetting in undermining good intentions. - Kristina R Olson (Public Library of Science (PLoS), 2013)
Evaluating others is a fundamental feature of human social interaction--we like those who help more than those who hinder. In the present research, we examined social evaluation of those who not only intentionally performed good and bad actions but also those to whom good things have happened (the lucky) and those to whom bad things have happened (the unlucky). In Experiment 1a, subjects demonstrated a sympathetic preference for the unlucky. However, under cognitive load (Experiment 1b), no such preference was expressed. Further, in Experiments 2a and 2b, when a time delay between impression formation (learning) and evaluation (memory test) was introduced, results showed that younger (Experiment 2a) and older adults (Experiment 2b) showed a significant preference for the lucky. Together these experiments show that a consciously motivated sympathetic preference for those who are unlucky dissolves when memory is disrupted. The observed dissociation provides evidence for the presence of conscious good intentions (favoring the unlucky) and the cognitive compromising of such intentions when memory fails.